The Female FTSE Report 2002: Women Directors moving Forward - Singh, Val; Vinnicombe, Susan (Cranfield University, 2002)
FTSE 100 COMPANIES THE GOOD NEWS: After two years of slippage, there is evidence that companies are again taking advantage of the diversity and talent that women directors can bring to their boards, by appointing new women. 61 companies now have women directors, up from 57 companies in 2001, but still not yet reaching the post-election “mini-boom” year 1999 when 64 companies had female directors. It is good to see that more companies have women executive directors, who now hold 3% of all executive board seats. In fact, women executive director numbers have increased by 50% since last year, up from 10 to 15. THE BAD NEWS: 88 of the UK’s top 100 companies still have no women executive directors. Chairmen and CEOs must take more responsibility for recruitment and development of their corporate talent pool to include women and diverse groups, to improve decision- making and bring variety and new voices into the boardroom. Indirectly, women directors act as powerful role models to younger, more junior female man